Revisiting Masuk Kaum: Contextualising Local Custom in Contemporary Islamic Family Law through ʿUrf and Maṣlaḥah - Miti Yarmunida; Yusmita; Zurifah; Akhmad Romadhon; Mahmoud Ali Al-Sobh (Faculty of Sharia, UIN Jurai Siwo Lampung, 2026)
Masuk Kaum, a customary practice among the Pekal community, illustrates how the legal validity of marriage under Islamic law and its social legitimacy within customary institutions operate in distinct yet interconnected normative spheres. Although the practice is not a formal requirement for marriage validity, it continues to play a significant role in regulating kinship relations and social integration after marriage. This study examines the contemporary practice of Masuk Kaum, evaluates its status as ʿurf, and assesses whether it promotes maṣlaḥah while avoiding mafsadah within the framework of contemporary Islamic family law. The research employs a doctrinal-empirical socio-legal approach based on fieldwork conducted in Sungai Rumbai District. Primary data were collected through semi-structured interviews with five key informants, supported by limited participant observation and field notes, while secondary data were drawn from classical and contemporary literature on uṣūl al-fiqh, particularly the concepts of ʿurf, maṣlaḥah, and maqāṣid al-sharīʿah. The data were analysed through thematic coding to identify the social functions of Masuk Kaum, followed by a doctrinal assessment against the criteria of ʿurf ṣaḥīḥ and maṣlaḥah. The findings demonstrate that Masuk Kaum functions primarily as a mechanism for incorporating spouses into the customary kinship system, enabling access to clan protection, participation in customary deliberation, and representation in communal dispute resolution. The practice qualifies as ʿurf ṣaḥīḥ insofar as it does not alter the essential pillars and legal conditions of marriage or create discriminatory exclusion. From the perspective of maṣlaḥah, it is categorised as serving the level of ḥājiyyāt because it strengthens kinship cohesion and contributes to conflict prevention. However, its legitimacy remains conditional, as compulsory financial obligations may constitute mafsadah when imposed without flexibility. This study contributes to contemporary Islamic family law by conceptualising ʿurf as a framework for normative recognition and maṣlaḥah as a critical standard for evaluating the legitimacy and sustainability of evolving customary practices.